Biosynthesis and characterization of nano magnetic hydroxyapatite (nMHAp): An accelerated approach using simulated body fluid for biomedical applications. Issue 17 (1st December 2020) - Bhatt, Akshay; Sakai, Kentaro; Madhyastha, Radha; Murayama, Masugi; Madhyastha, Harishkumar; Rath, Subha Narayan
Abstract: There are several metal ions including iron oxide nanoparticles, which has been used for doping hydroxyapatite to overcome the existing shortcoming associated with poor mechanical strength, less bioactivity and inert properties. Iron oxide nanoparticles, commonly known as magnetite, has shown a great potential in tissue engineering and various other biomedical applications. It has been proven that small quantity of iron increases the mechanical properties as well antioxidative property of the material. Magnetic hydroxyapatite is synthesized by many different synthesis routes such as hydrothermal, spray drying, ultrasonic irradiation etc. These synthesis routes are time consuming and requires sophisticated process parameters. Hence, to overcome these complexities, this study aims to synthesize and characterize nano magnetic hydroxyapatite (nMHAp) in a shorter duration than the conventionally used duration (over 24 h) through a novel bio-mimetic approach. The physicochemical properties were checked using XRD, FTIR, TGA, XPS, DLS, SEM, TEM and VSM. The results suggest that synthesized nMHAp contains magnetic properties and resembles carbonated apatite with the traces of Na, Mg, K, Cl and Fe. SEM and TEM analysis confirmed the spherical nature of nMHAp with average size between 10 and 200 nm. The optimized average time for nMHAp synthesis was found to be 3 h. Cellular biocompatibility and the measurement of reactive oxygen species using L929 cells confirmed the biocompatible and antioxidative nature of nMHAp. Hence, Our studies show that the nMHAp can be synthesized biomimetically in 3 h and potentially could be used for bone tissue engineering and other biomedical applications. Graphical abstract: Image 1